2019
DOI: 10.1038/s41598-019-54616-x
|View full text |Cite
|
Sign up to set email alerts
|

Schinus terebinthifolia leaf lectin (SteLL) has anti-infective action and modulates the response of Staphylococcus aureus-infected macrophages

Abstract: Staphylococcus aureus is recognized as an important pathogen causing a wide spectrum of diseases. Here we examined the antimicrobial effects of the lectin isolated from leaves of Schinus terebinthifolia Raddi (SteLL) against S. aureus using in vitro assays and an infection model based on Galleria mellonella larvae. The actions of SteLL on mice macrophages and S. aureus-infected macrophages were also evaluated. SteLL at 16 µg/mL (8 × MIC) increased cell mass and DNA content of S. aureus in relation to untreated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 71 publications
0
3
0
Order By: Relevance
“…Brito et al [4] demonstrated the safety of ApuL with regards to human lymphocytes, while Santos et al [11] showed that SteLL (3.12-50 µg/mL) is not cytotoxic for mouse splenocytes. Additionally, the viability of macrophages isolated from mice was not affected by SteLL (2.0-16.0 µg/mL) [60].…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Brito et al [4] demonstrated the safety of ApuL with regards to human lymphocytes, while Santos et al [11] showed that SteLL (3.12-50 µg/mL) is not cytotoxic for mouse splenocytes. Additionally, the viability of macrophages isolated from mice was not affected by SteLL (2.0-16.0 µg/mL) [60].…”
Section: Discussionmentioning
confidence: 92%
“…In previous studies, SteLL (12.5 µg/mL) demonstrated the ability to stimulate the release of cytokines (IL-6, IL-10, IL-17A, TNF-α), NO, and superoxide anion in cultured macrophages isolated from mice. In addition, it stimulated the production of IL-17A, TNF-α, IFN-γ, IL-4, and IL-2 in cultured splenocytes isolated from mice [11,60]. It has already been shown that ApuL is capable of inducing lymphocytes isolated from humans to produce a Th17 response, producing IL-17 and IL-10, the latter with an immunoregulatory function [4].…”
Section: Discussionmentioning
confidence: 97%
“…Staphylococcus aureus ATCC 6538 cells (~2 × 10 7 CFU/mL) were inoculated into LB medium (2 mL) in 14-mL tubes and incubated for 24 h at 37°C with 13- cis -retinoic acid (0, 10, 20, 50, or 100 μg/mL) with shaking at 250 rpm. Staphyloxanthin levels were assessed optically, as previously described ( De Souza Feitosa Lima et al, 2019 ; Kim et al, 2022a ).…”
Section: Methodsmentioning
confidence: 99%
“…These compounds act by interrupting the molecular synthesis and microbial cell cycle [ 205 , 206 , 207 ]. Several natural products are also reported to have promising in vivo antimicrobial activity against S. aureus , including in models of wound infections [ 208 , 209 , 210 , 211 ].…”
Section: Eskape and Wound Infectionsmentioning
confidence: 99%